Ae1/Sbe1 maize-derived high amylose improves gut barrier function and ameliorates type II diabetes in high-fat diet-fed mice by increasing Akkermansia - Qi, Weiwei; Liu, Jingchao; Yu, Tante; Huang, Shengchan; Song, Rentao; Qiao, Zhenyi (Frontiers in Nutrition, 2022)
Type II diabetes mellitus (T2DM) has its origins in chronic inflammation due to immune dysregulation. Improving chronic inflammation can significantly reduce the probability of T2DM and the rate of disease progression. Resistance to starch 2 (RSII) high-amylose maize starch (HAMS) has been widely implicated in the improvement and regulation of T2DM. However, its exact molecular mechanisms have not been fully discovered. Here, we used CRISPR/Cas9 technology to knock out two starch-branching enzyme genes, Ae1 and Sbe1, in maize to obtain mutants containing higher levels of HAMS. In experiments in which HAMS was fed to mice on a high-fat diet (HFD), we confirmed the function of HAMS in ameliorating hyperglycemia. Mechanistically, we found that HAMS improves the gut barrier function by increasing the Akkermansia abundance in the gut. This increase led to the alleviation of chronic inflammation in mice on a HFD, resulting in improved insulin sensitivity and a decrease in blood glucose.